Complete mitochondrial genome of Anthus richardi (Passeriformes: Motacillidae). Issue 1 (2nd January 2019) - Wang, Longfei; Dong, Yuanqiu; Xuan, Jun; Zhang, Fengling; Fu, Rong; Liu, Gang; Xiang, Xingjia; Zhou, Lizhi
Abstract: Richard's Pipit Anthus richardi is a medium-sized passerine bird which breeds in open grasslands in northern Asia with a long-distance migrant moving to open lowlands in the Indian subcontinent and Southeast Asia. In this study, the mitochondrial genome of this bird species was obtained by the PCR-based sequencing method. The mitogenome is 16, 871 bp in size, including 22 tRNAs, 2 rRNAs, 13 protein-coding genes and a D-loop. The A, T, G, and C base composition of the mitochondrial DNA are 29.73%, 23.12%, 14.59% and 32.56%, respectively. The starting codon of protein-coding genes is typical ATG, except for the ND2 which starts with ATA. The D-loop locates between genes of tRNA Glu and tRNA Phe . The result of the phylogenetic analysis indicates that A. richardi has close phylogenetic relationship with A. novaeseelandiae .